The Contents of Catechins and Anthocyanins in the Above-Ground Organs of Plants of Prunus spinosa L. - Levon, Volodymyr (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
Carrying out phenological and biochemical studies, the prospect of using the studied varieties of a thorn in breeding programs for obtaining new adaptive, large-fruited varieties and cultivars have been established. The data on the content of catechins and anthocyanins in the bark, leaves, flowers, and fruits of cultivated plants and wild varieties of Prunus spinosa L. are presented. As a result of the study, it was found that the wild variety of Prunus spinosa has a significantly higher content of anthocyanins and catechins in the above-ground organs than cultural varieties. This indicates a higher adaptive capacity of wild varieties to unfavorable environmental factors in comparison with cultural varieties, as catechins and anthocyanins, as well as other representatives of flavonoids, are used as biochemical markers of species adaptability. According to the content of anthocyanins and catechins can predict the success of the introduction. The highest amount of catechins and anthocyanins found in the leaves. The flowers have the lowest content of anthocyanins and catechins. In the study of the contents of catechins and anthocyanins in fruits of plants cultivated and wild varieties of Prunus spinosa. It was found that the wild variety of Prunus spinosa (genotype Sp1) has the lowest content of catechins in the presence of the highest content of anthocyanins.